Assessing Energy Price Induced Improvements in Efficiency of Capital in OECD Manufacturing Industries - Steinbuks, Jevgenijs; Neuhoff, Karsten (World Bank, Washington, DC, 2014)
To assess how capital stocks adapt to energy price changes, it is necessary to account for the impacts on different vintages of capital and to account separately for price-induced and autonomous improvements in the energy efficiency of capital stock. The results of econometric analysis for five manufacturing industries in 19 OECD countries between 1990 and 2005 indicate that higher energy prices resulted in smaller energy use due to both improved energy efficiency of capital stock and reduced demand for the energy input. The investment response to energy prices varied considerably across manufacturing industries, being more significant in energy-intensive sectors. The results of policy simulations indicate that a carbon tax can deliver significant reductions in energy consumption in the medium run with modest declines in energy-using capital stock.